Desigualdad laboral como forma de violencia contra las mujeres en el Ecuador - Moreira-Intriago, María Dolores; Cajas-Párraga, Cinthia Mariela; Moreno-Arvelo, Pamilys Milagros (IUSTITIA SOCIALIS, 2022)
Desigualdad laboral como forma de violencia contra las mujeres en el Ecuador